A functional interaction between TRPC/NCKX induced by DAG plays a role in determining calcium influx independently from PKC activation. (November 2013) - Pulcinelli, Fabio M.; Trifirò, Elisabetta; Massimi, Isabella; Di Renzo, Livia
<x xml:space="preserve">Abstract</x> Ca2+influx might occur through K+-dependent Na+/Ca2+ exchanger operating in reverse mode (rNCKX). In a cellular model different from platelets, an interaction between canonical transient receptor potential cation (TRPC) channels and NCX has been found. The aim of this study was to verify whether the TRPC/NCKX interaction operates in human platelets. Our results showed that the diacylglycerol (DAG) analogue, 1-oleoyl-2-acetyl-sn-glycerol (OAG) induced rNCKX-mediated Ca2+ influx through TRPC-mediated Na+ influx. DAG-induced activation of TRPC/NCKX occurs independently of protein kinase C (PKC) activation, as PKC inhibitor did not modify OAG-mediated Ca2+ influx. Moreover, as both rNCKX and TRPC inhibitors reduced OAG-induced platelet aggregation which, conversely, was increased by flufenamic acid, known to develop TRPC activity, it could be suggested that the TRPC/NCKX interaction has a role in OAG-dependent platelet aggregation.